An Exemestane Derivative, Oxymestane-D1, as a New Multi-Target Steroidal Aromatase Inhibitor for Estrogen Receptor-Positive (ER+) Breast Cancer: Effects on Sensitive and Resistant Cell Lines - Amaral, Cristina (2023)
Around 70-85% of all breast cancer (BC) cases are estrogen receptor-positive (ER+). The third generation of aromatase inhibitors (AIs) is the first-line treatment option for these tumors. Despite their therapeutic success, they induce several side effects and resistance, which limits their efficacy. Thus, it is crucial to search for novel, safe and more effective anti-cancer molecules. Currently, multi-target drugs are emerging, as they present higher efficacy and lower toxicity in comparison to standard options. Considering this, this work aimed to investigate the anti-cancer properties and the multi-target potential of the compound 1α,2α-epoxy-6-methylenandrost-4-ene-3,17-dione (Oxy), also designated by Oxymestane-D1, a derivative of Exemestane, which we previously synthesized and demonstrated to be a potent AI. For this purpose, it was studied for its effects on the ER+ BC cell line that overexpresses aromatase, MCF-7aro cells, as well as on the AIs-resistant BC cell line, LTEDaro cells. Oxy reduces cell viability, impairs DNA synthesis and induces apoptosis in MCF-7aro cells. Moreover, its growth-inhibitory properties are inhibited in the presence of ERα, ERβ and AR antagonists, suggesting a mechanism of action dependent on these receptors. In fact, Oxy decreased ERα expression and activation and induced AR overexpression with a pro-death effect. Complementary transactivation assays demonstrated that Oxy presents ER antagonist and AR agonist activities. In addition, Oxy also decreased the viability and caused apoptosis of LTEDaro cells. Therefore, this work highlights the discovery of a new and promising multi-target drug that, besides acting as an AI, appears to also act as an ERα antagonist and AR agonist. Thus, the multi-target action of Oxy may be a therapeutic advantage over the three AIs applied in clinic. Furthermore, this new multi-target compound has the ability to sensitize the AI-resistant BC cells, which represents another advantage over the endocrine therapy used in the clinic, since resistance is a major drawback in the clinic.